2021
DOI: 10.1093/molehr/gaab024
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of parturition: insights from gene regulation studies in the myometrium

Abstract: The onset of labour is a culmination of a series of highly coordinated and preparatory physiological events that take place throughout the gestational period. In order to produce the associated contractions needed for fetal delivery, smooth muscle cells in the muscular layer of the uterus (i.e. myometrium) undergo a transition from quiescent to contractile phenotypes. Here, we present the current understanding of the roles transcription factors play in critical labour-associated gene expression changes as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 135 publications
1
17
0
Order By: Relevance
“…As they stand, our findings are important to consider in light of potential therapeutic applications that can be developed to address the critical health challenges associated with early labor onset. For instance, as we previously discussed [13], attempts to target MYB with different drugs or compounds to downregulate its activity in the context of treating acute myeloid leukemia have been met with some success [29][30][31]. Of course, therapeutic treatment of human extreme preterm birth may mandate somewhat different strategies than that of cancer.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…As they stand, our findings are important to consider in light of potential therapeutic applications that can be developed to address the critical health challenges associated with early labor onset. For instance, as we previously discussed [13], attempts to target MYB with different drugs or compounds to downregulate its activity in the context of treating acute myeloid leukemia have been met with some success [29][30][31]. Of course, therapeutic treatment of human extreme preterm birth may mandate somewhat different strategies than that of cancer.…”
Section: Plos Onementioning
confidence: 99%
“…More recent studies have shown preliminary evidence of co-operation between the more well-established transcription factor quartet and other candidate factors less well-known in this context, such as members of the KLF, SMAD, FOXO, IRF, and HOXA families (reviewed in [ 13 ]). Despite these initial advances in identifying putative members of gestational stage-specific transcription factor complexes, the full repertoire of proteins that contribute to the laboring phenotype in SMCs is not comprehensively characterized.…”
Section: Introductionmentioning
confidence: 99%
“…However, as they stand, these findings are important to consider in light of potential therapeutic applications that can be developed to address the critical health challenges associated with early labour onset. For instance, as we previously discussed [9], attempts to target MYB with different drugs or compounds to down-regulate its activity in the context of treating acute myeloid leukemia have been met with some success [23][24][25]. Of course, therapeutic treatment of human extreme preterm birth may mandate somewhat different strategies than that of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many members of the highlighted transcription factor quartet exhibit consistent expression levels and alter their activity at labor onset due to a change in post-translational modifications. However, most of these novel candidate proteins are themselves differentially expressed between pre-laboring and active laboring time points in mouse and/or human term and preterm models (reviewed in [9]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation